Effect of Task Aversiveness and Student Academic Procrastination - Syahrial, Melva; Netrawati, Netrawati; Sukma, Dina; Ardi, Zadrian (Universitas Negeri Padang, 2022)
This study is objective to describe the task aversiveness and procrastination of academics, to analyze the influences between task aversiveness to procrastination of academics and to analyze the relationship between task aversiveness to procrastination of academics. This research uses descriptive quantitative research methods. Identification of the problem in the study, there is a correlation between procrastination and task aversiveness separately strong and stable. The Purpose of study is test of connection task aversiveness student with procrastination academic. In this study, researchers use a quantitative method with a descriptive correlative approach. The population in their study were 575 students.Amount sample in this study was 236 students which was taken by using Slovin formula. The Sample was taken from each different class, then the Proportional Stratified Random Sampling technique was used. On this research, there are two types of variables. They are variable free (independent) and variable bound (dependent). As for the free variable or the independent variablein this study is task aversiveness, while the bound variable or the dependent variable is academic procrastination. In this study, the data used is interval data. As for variable in this study is task aversiveness and procrastination academic. The research instrument used is a questionnaire using Likert Scale. The results of this research show 64.41 % of students have high task aversiveness. This shows that students who perceive task aversion bothered or are not comfortable with duty are in the high category. On procrastination academic shows 60.59 % have high academic procrastination behavior. This shows the behavior of procrastination academic student high category because many procrastinating students do academic duty in the period of time you want. From the hypothesis it is found that task aversion influences significantly to the procrastination of academics. We conclude that they are connection task aversiveness significantly to academic procrastination behavior . That is, the more and more high task aversiveness, then the behavior of academic procrastination will also increase, and vice versa .